Grazing intensity and driving factors affect soil nitrous oxide fluxes during the growing seasons in the Hulunber meadow steppe of China. (26th April 2016) - Yan, Ruirui; Tang, Huajun; Xin, Xiaoping; Chen, Baorui; Murray, Philip J; Yan, Yunchun; Wang, Xu; Yang, Guixia
Abstract: In this study, the effects of cattle grazing intensity on soil nitrous oxide (N2 O) fluxes were examined in the Hulunber meadow steppe of north-eastern China. Six stocking-rate treatments (0, 0.23, 0.34, 0.46, 0.69, and 0.92 AU ha −1 ) with three replicates were established, and observations were conducted from 2010 to 2014. Our results showed that substantial temporal fluctuations in N2 O flux occurred amongst the different grazing intensities, with peak N2 O fluxes after natural rainfall. Grazing had a long-term effect on the soil N2 O flux in the grasslands. After 4–5 years of grazing, the N2 O fluxes under increased levels of grazing intensity began to decrease significantly by 31.4%–60.2% in 2013 and 32.5%–50.5% in 2014 compared to the non-grazing treatment. We observed a significant negative linear relationship between the soil N2 O fluxes and grazing intensity for the five-year mean. The soil N2 O flux was significantly affected each year in all of the treatments. Over the five years, the temporal coefficient of variation (CVs) of the soil N2 O flux generally declined significantly with increasing grazing intensity. The soil N2 O emission rate was significantly positively correlated with soil moisture (SM), soil available phosphorus (SAP), soil NH 4 + -N, soil NO 3 − -N, above-ground biomass (AGB), plant ground cover and height and was negatively correlated with total soil nitrogen (TN). Stepwise regressions showed that the N2 O flux was primarily explained by SM, plant height, TN, soil pH, and soil NH 4 + -N. Using structural equation modelling, we show that grazing significantly directly influenced the plant community and the soil environment, which then influenced the soil N2 O fluxes. Our findings provide an important reference for better understanding of the mechanisms and identifying the pathways of grazing effects on soil N2 O emission rates, and the key drivers plant community and soil environment within the nitrogen cycle that are mostly likely to affect N2 O emissions in the Inner Mongolian meadow steppes.